The Effect of Formula Modisco Supplementation on Weight Gain in Malnourished Toddlers In the Kendari City Health Center: Malnourished Toddlers - Sari Arie Lestari B.; Islaeli Islaeli; Nawawi Nawawi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: There were 32 cases of malnourished children in 2022 at the Kendari City Health Center. Formulas Modisco can be used as a supplementary food to improve the weight of malnourished children. The aim of this research is to determine the influence of Modisco formula on the weight gain of malnourished children. The variables in this study are Modisco formula and the increase in weight of malnourished children. Methods: The population in this study is malnourished children, and a total of 32 children were sampled by using total sampling technique. The research design was used a one-group pretest-posttest pre-experimental study and using paired t-test analysis. Results: The statistical test results showed that the alpha value was < 0.05, which is 0.000, indicating that there is an influence of Modisco formula on the weight gain of malnourished children. Conclusion: It is recommended to promote the use of Modisco formula as a supplementary food for malnourished children and to modify the formula by incorporating local ingredients to create snacks for children.